Patriarchal Tradition in Jane Austen’s Pride and Prejudice - BR Surbakti, Jastri Yani; Rorintulus, Olga; Tuerah, Ignatius J. C. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
The aim of this research focuses on analyzing the patriarchal tradition in Jane Austeen's Pride and Prejudice, as well as concluding what impacts will happen to women with the existence of a patriarchal tradition system. This research uses a Feminist literary approach which studies something using gender as the main analytical category in a research.Researcher has analyzed two selected the peimary and secondary data, and to conduct more comprehensive research. To analyze this research, researcher used descriptive qualitative research methods. From the data that researcher have found, there are patriarchal traditions that exist in the novel as well as gender disparities between the rights that women and men have in terms of choosing a life partner, education, politics, and inheritance ownership rights that only men have. This research discusses the patriarchal tradition which considers men as superior and women as inferior